KEEFEKTIFAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DENGAN TIPE TGT UNTUK MENINGKATKAN HASIL BELAJAR DAN KARAKTER SISWA SD - Ari Wibowo (Universitas PGRI Yogyakarta, 2015)
ABSTRACT The aims of this research were (1) to find out the difference of effectivenessbetween cooperative learning model type STAD and type TGT towards students’achievement in civics class, and (2) to find out the difference of effectiveness betweenmodel type STAD and type TGT towards students’ characters in terms of cooperation,responsibility, and empathy. This research was a quasi-experiment research study tocompare value clarification method to conventional method in civics class. Thepopulation in this research were grade 5th students in SD Padokan, Kasihan, Bantul. Thesampling technique used was random sampling. The data was gathered by giving multiplechoice tests to measure students’ academic result and Likert scale to measure students’characters. To find out about whether the questions were valid or not, product momentwas used, while for reliability of the questions, Cronbach Alpha was used. Furthermore,for the prerequisite for normality of the data, Kolmogorov Smirnov Z was used, whereasLevene test was used to prove the homogeneity of students’ academic achievement. Thedata of students’ achievement and characters was analyzed by using independent samplet-test. The result of the result shows that (1) students’ academic results in civics classbetween the experiment and control group are significantly different. It is proven by theanalysis result of independent sample t-test which reveals that t observed > ttable (2,343 >2,000), (2) there are significant differences towards students’ characters which includsresponsibility, cooperation, and empathy. It is proven by the analysis result ofindependent sample t-test which reveals that t observed > ttable (2,486 > 2,000). From thecomparison, it can be concluded that the score of students’ academic result in civics classand students’ characters in the experiment group is higher than control group. In otherwords, the use of cooperative learning model type STAD was more effective than typeTGT.